Effects of in vitro fermentation of barley β‐glucan and sugar beet pectin using human fecal inocula on cytokine expression by dendritic cells. Issue 1 (11th August 2016) - Rösch, Christiane; Taverne, Nico; Venema, Koen; Gruppen, Harry; Wells, Jerry M.; Schols, Henk A.
Abstract : Dietary fibres influence the immune system. This stimulation by dietary fibres might be influenced by present endotoxins such as LPS. By using bone marrow derived dendritic cells (BMDCs) from TLR2/4 knockout mice, this undesired stimulation was circumvented and controls containing only microbiota did not cause any TNF induction in the BMDCs. In contrast, samples containing fibres (e.g. β‐glucan (left) or sugar beet pectin (right)) induced immune response in different ways depending on the fibres. In addition, glycosidic fibre degradation products induced even higher amounts of TNF, depending on the fermentation stage (0–48 hours). Abstract : Scope: This study simulates the fermentation process of barley β‐glucan and sugar beet pectin in the human colon and monitors the degradation products formed. Additionally, immune effects of the degradation products were investigated. Methods and results: Immunostimulatory activity of fermentation digesta was investigated using bone marrow derived dendritic cells (BMDCs) from toll‐like receptor 2/4 (TLR2/4) knockout mice, which were unresponsive to microbe‐associated molecular patterns. Cytokine responses were elicited to dietary fibers and not to the SCFA and microbiota. The fermentation digesta were analyzed for their SCFA profiles and glycan metabolites over time. During fermentation the amount of insoluble precipitating fibers increased and induced as well as soluble molecules of lower molecular mass greater amounts of cytokines in BMDCs than the parental fiber. Additionally, high amounts of cytokines can be attributed to soluble galactose‐rich beet pectin molecules. Conclusions: The fermentation of the two fibers led to fiber‐specific amounts of SCFA, glycosidic metabolites, and different immunomodulatory properties. BMDC from TLR2/4 knockout mice did not respond to the digest microbiota and SCFA, making it a useful approach to study temporal effects of fermentation on the immunomodulatory effects of fibers.